AJARAN SOSIAL GEREJA TENTANG MEMBANGUN KELUHURAN MARTABAT MANUSIA SEBAGAI CITRA ALLAH - Toron, Vinsensius Bawa; Marinus, Yohanes (STP St. Bonaventura Medan, 2018)
Many kinds of policy and program should be deeply rooted in our belief to God and for people prosperity themselves. Empowerment which is involve worship is meaningful if it is directed to human prosperity as God creature which is him alike. Church social doctrine which is printed in encyclical emphasize that the process of empowerment does not make them having attitude of dependency to power of a big scale economic or government, but escape them from dependency. There for encyclical contains that PSE commission should develop people skill and potential so that they are able to create independent economic business, and PSE commission should control public policy direction in economic or politics in order to strengthen public prosperity (bonum commune). PSE commission should be able to push public policy creator and doer to work honestly, fair, and concern about common interest. Creating network marketing and business micro which train and creating work place for who are not skillful enough. This action should be developed and facilitated further, so that group business which have got skill training about farming and craft are able to market business result.